2012
DOI: 10.3390/molecules17033291
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative, Antimicrobial and Apoptosis Inducing Effects of Compounds Isolated from Inula viscosa

Abstract: Abstract:The antiproliferative and antimicrobial effects of thirteen compounds isolated from Inula viscosa (L.) were tested in this study. The antiproliferative activity was tested against three cell lines using the MTT assay. The microdilution method was used to study the antimicrobial activity against two Gram positive bacteria, two Gram negative bacteria and one fungus. The apoptotic activity was determined using a TUNEL colorimetric assay. Scanning electron microscopy was used to study the morphological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 34 publications
2
74
0
7
Order By: Relevance
“…Even though there are precedents in the literature about the antibacterial activity exerted by compound 2 against E. coli and against some methicillin-susceptible and methicillin-resistant S. aureus (Hirai et al 2010;Kuete et al 2011), other authors reported a lack of effectiveness (Hossion et al 2010;Li et al 2009) matching that obtained in this work. The level of activity shown by compound 3 against E. coli and S. aureus, does not match that found by Van Puyvelde et al (1989), but it does agree with the results obtained by Talib et al (2012) in a microtiter plate dilution test performed against E. coli. Discrepancies in the effectiveness of flavonoids have been attributed to differences in the solubility of these compounds, in the conditions of the assays performed and in the judgment of the MICs (Cushnie and Lamb 2005;Wu et al 2008).…”
Section: Determination Of Mics and Mbcssupporting
confidence: 76%
“…Even though there are precedents in the literature about the antibacterial activity exerted by compound 2 against E. coli and against some methicillin-susceptible and methicillin-resistant S. aureus (Hirai et al 2010;Kuete et al 2011), other authors reported a lack of effectiveness (Hossion et al 2010;Li et al 2009) matching that obtained in this work. The level of activity shown by compound 3 against E. coli and S. aureus, does not match that found by Van Puyvelde et al (1989), but it does agree with the results obtained by Talib et al (2012) in a microtiter plate dilution test performed against E. coli. Discrepancies in the effectiveness of flavonoids have been attributed to differences in the solubility of these compounds, in the conditions of the assays performed and in the judgment of the MICs (Cushnie and Lamb 2005;Wu et al 2008).…”
Section: Determination Of Mics and Mbcssupporting
confidence: 76%
“…The choice of our investigated plants is based on two criteria: first, in this domain there is no study in Algeria that deals with these plants, and the second criterion is that these plants have ethnopharmacological data indicating their traditional utilization in the treatment of different diseases and disorders (Paula de Oliveira et al, 2011). In addition, some of them have been proved to be efficient in the treatment of various cancerous lesions (Xavier, Lima, Fernandes-Ferreira, & Pereira-Wilson, 2009;Aissaoui, Zizi, Israili, & Lyoussi, 2011;Sertel, Eichhorn, Plinkert, & Efferth, 2011;Talib, Zarga, & Mahasneh, 2012) and as potential neuroprotectants (Vora, Patil, & Pillai, 2009;Kelsey, Wilkins, & Linseman, 2010;Pacifico et al, 2013;Pacifico et al, 2014). Due to their traditional utilization and active components, these plants are also considered to be efficient for the treatment of free radical-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Selecive antiproliferative and proapoptotic capacity in breast cancer cells; cytotoxic and genotoxic effect in A. cepa. Hypoglycemic properties via stimulation of glucose uptake Afifi-Yazar et al 2011;Talib et al 2012;Seca et al 2014). Antimicrobial and anti-Helicobacter pylori efficacies (Karygianni et al 2014;Masadeh et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Antifeedant activity of its pyrrolizidine alkaloids (Sicilliano et al 2005). Antidiabetic activity of its aqueous extract in STZ-diabetic rats (Muhammed & Ari 2012;Al-Snafi 2014 Talib et al 2012); chlorogenic-and caffeic acids, rutin, myricetin, quercetin, luteolin and kaempferol (Gökbulut et al 2013); bi-and tri-cyclic sesquiterpene lactones; inuloxins A-D (Andolfi et al 2013). …”
Section: Introductionmentioning
confidence: 99%